Child‐Care Instability and Behavior Problems: Does Parenting Stress Mediate the Relationship?. Issue 5 (7th June 2017) - Pilarz, Alejandra Ros; Hill, Heather D.
Abstract : Child‐care instability is associated with more behavior problems in young children, but the mechanisms of this relationship are not well understood. Theoretically, this relationship is likely to emerge, at least in part, because care instability leads to increased parenting stress. Moreover, low socioeconomic status and single‐mother families may be more vulnerable to the effects of instability. This study tested these hypotheses using data from the Fragile Families and Child Wellbeing study ( N = 1, 675) and structural equation modeling. Three types of child‐care instability were examined: long‐term instability, multiplicity, and needing to use back‐up arrangements. Overall, findings showed little evidence that parenting stress mediated the associations between care instability and child behavior problems among the full sample. Among single‐mother and low‐income families, however, needing to use back‐up arrangements had small positive associations with parenting stress, which partially mediated the relationship between that type of care instability and child externalizing behavior problems.